Tác động của đổi mới sáng tạo đến ba trụ cột phát triển bền vững: Nghiên cứu các doanh nghiệp ICT Việt Nam - Mai Thanh, Thủy; Đặng Thị Việ, Đức (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study aims to explore the relationship between innovation and the three pillars of sustainability performance (economic, environmental, and social) in Vietnamese information and communication technology (ICT) enterprises. The study used the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to assess the impact of process innovation and product innovation on sustainability performance, based on survey data from 254 ICT firms. The results show that process innovation has a substantial impact on all aspects of sustainability performance. Meanwhile, product innovation affects economic and environmental performance, but the effect on social performance is not statistically significant. These findings provide additional empirical evidence from an emerging market such as Vietnam and recommend that ICT enterprises focus on process innovation and reconsider their product innovation strategies to achieve comprehensive sustainable performance.